Lateral Hypothalamic Orexin Neurons Mediate the Reward Effects of Pain Relief Induced by Electroacupuncture - Wang, Can; Chen, Meiyu; Qin, Chuan; Qu, Xiaoyi; Shen, Xueyong; Liu, Sheng (Frontiers in Molecular Neuroscience, 2022)
The reward of pain relief caused by acupuncture has been found to be clinically significant. However, the molecular mechanisms underlying acupuncture-induced reward of pain relief in chronic pain remain unclear and have not been analyzed in suitable preclinical models. Here, we investigated whether acupuncture could potentially induce the reward of pain relief and orexin neuronal signaling in the lateral hypothalamus (LH) and exhibit a possible role in electroacupuncture (EA)-induced reward in spared nerve injury (SNI) rats. Therefore, by using conditioned place preference (CPP) paradigm, we noticed that EA induced the preference for cues associated with EA-induced pain relief in the early, but not late, phase of chronic pain. These observations were different from the immediate antihyperalgesic effects of EA. c-Fos/orexin double labeling revealed that EA stimulation on 14 days but not on 28 days after SNI modeling activated greater numbers of c-Fos positive orexin neurons in the LH after the CPP test. Moreover, the administration of an orexin-A antagonist in the LH significantly blocked the reward effects of pain relief induced by EA. Furthermore, by using cholera toxin b subunit combined with c-Fos detection, we found that the orexin circuit from the LH to the nucleus accumbens (NAc) shell was significantly activated after EA induced CPP. Microinjection of the orexin antagonist into the NAc shell substantially attenuated the CPP induced by EA. Intravenous injection of low-dose orexin-A together with EA resulted in significantly greater antihyperalgesia effects and CPP scores. Together, these findings clearly demonstrated that LH orexin signaling could potentially play a critical role in the reward effects of pain relief induced by acupuncture. The observations of the present study extended our understanding of orexin signaling in the LH and its role in EA-induced reward, providing new insights into the mechanisms of acupuncture analgesia.